Student, Faculty, and Coach Perspectives on Why Athletes Excel in Medical School: A Qualitative Analysis. Issue 1 (20th January 2022) - Strowd, Lindsay Chaney; Kelly, Katherine; Peters, Timothy R.; Jackson, Jennifer Marie
Abstract: Phenomenon Medical schools are tasked with selecting applicants who will excel in a rigorous curriculum and successfully perform as future physicians. While many studies have assessed quantitative prematriculation data for predicting success in medical school, fewer studies have assessed for qualitative prematriculation factors influencing medical school performance. A recent study revealed that medical students with at least one year of varsity level college athletics participation outperformed their peers on United States Medical Licensing board exams and clinical clerkships. The current study sought to explore medical student, medical school faculty, and college coach perspectives about factors explaining why medical students with collegiate athletic experience succeed in medical school. Approach: In 2019, the authors conducted semi-structured interviews with medical students with collegiate athletic experience, medical school faculty with experience educating student athletes, and college coaches with experience training student athletes who matriculated into medical school. The interview transcripts were systematically coded and analyzed for themes using a grounded theory approach. Participants were recruited and interviewed until saturation of data was reached. Findings: Fifteen medical students with collegiate athletic experience, five medical school faculty, and three collegiate coaches participated in the study. Six themes were identified as important factors explaining the academic success of these students in medical school and each of these themes appeared in student, faculty, and coach interviews: goal setting, goal pursuit, and performance appraisal; development of time management, planning, and organizational skills; development of team values and teamwork skills; development of communication and interpersonal skills; acceptance of, coping strategies for, and resilient response to stress and adversity; and prioritization of personal wellness. Participants described meaningful connections between these attributes and skills, suggesting the students' development, transfer, and application of them is interrelated. Insights : In this study, academic success of medical students with collegiate athletic experience was attributed to specific skills and attributes developed during college. The grounded theory life skills transfer model can explain transfer of these attributes and skills from college to the medical school setting. Theoretical frameworks and empirical study findings from the sociology, educational psychology, sports psychology, and medical education literature provide helpful lenses for understanding why these skills and attributes confer success among student athletes in medical school. These findings offer important insights on skill development that may support the academic success of all medical students.